1997
DOI: 10.1021/jp962696h
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of CO2 with H2O on Titanium Oxides Anchored within Micropores of Zeolites:  Effects of the Structure of the Active Sites and the Addition of Pt

Abstract: Titanium oxide species anchored within the Y-zeolite cavities by an ion-exchange method exhibit a high and unique photocatalytic reactivity for the reduction of CO2 with H2O at 328 K with a high selectivity for the formation of CH3OH in the gas phase. The in situ photoluminescence, ESR, diffuse reflectance absorption, and XAFS (XANES and FT-EXAFS) investigations indicate that the titanium oxide species are highly dispersed within the zeolite cavities and exist in a tetrahedral coordination. The charge transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
245
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(256 citation statements)
references
References 28 publications
10
245
0
1
Order By: Relevance
“…the intermediates to generate CH 3 OH. Anpo et al (1997) reported a unique role of Pt metal on Ti/Y-zeolites for CO 2 photoreduction, besides the conventional role of Pt in promoting charge transfer. They found that carbon radials and H atoms were generated on the same Pt metal sites, and thus CH 4 formation was facilitated by Pt.…”
Section: Product Selectivitymentioning
confidence: 99%
“…the intermediates to generate CH 3 OH. Anpo et al (1997) reported a unique role of Pt metal on Ti/Y-zeolites for CO 2 photoreduction, besides the conventional role of Pt in promoting charge transfer. They found that carbon radials and H atoms were generated on the same Pt metal sites, and thus CH 4 formation was facilitated by Pt.…”
Section: Product Selectivitymentioning
confidence: 99%
“…Scientific challenges in the domain of storing solar energy by CO 2 conversion are larger than for hydrogen synthesis. CO 2 conversion in the presence of water can lead to different products, such as methane or methanol, and little is known about the role of the chemical composition and surface structure of electrocatalytic and photo-catalytic converters in triggering selectivity [19][20][21][26][27][28][29]. In the following case studies we will further address the options for chemical storage of solar energy.…”
Section: Minerals (Including P and N In Suitable Formmentioning
confidence: 99%
“…While some interesting results have been reported, productivity is still beyond the limit to design a viable process. Besides studies on crystalline TiO 2 based catalysts, Ti-containing siliceous materials, such as TS-1, Ti-MCM-41, Ti-MCM-48 and Ti-SBA-15 were found to yield high methane production rates in gas phase photocatalytic CO 2 reduction [5,[26][27][28][29]. The production yield of highly dispersed titanium oxide catalysts (in mol/g-Ti/h), was increased 10-300 times as compared to crystalline TiO 2 .…”
Section: Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…Therefore, the photocatalytic hydrogenation of CO2 upon semiconductor powders has received much attention [9][10][11][44][45][46][47][48][49][50][51][52][53][54][55][56]. Among the earliest studies on the photocatalytic hydrogenation of CO2, Inoue et al examined a wide range of semiconductors (WO3, TiO2, ZnO, CdS, GaP, and SiC in 200 -400 mesh) in aqueous solution [44].…”
Section: Hydrogenation Of Carbon Dioxidementioning
confidence: 99%
“…Among those, methanol is the most valuable product because it can be directly used as a fuel or a building block. High efficiency and selectivity in the preparation of methanol were obtained by the use of Ti-oxide/Y-zeolite catalysts containing highly dispersed tetrahedral titanium oxide species under UV irradiation [53,54]. The charge-transfer excited state of these species played an important role in the selectivity for producing CH3OH, in contrast to the different selectivity giving CH4 on bulk TiO2 photocatalyst.…”
Section: Hydrogenation Of Carbon Dioxidementioning
confidence: 99%